Inter-hemispheric coupling during sudden stratospheric warming events with elevated stratopause - Athreyas, Kashyapa Naren (2022)
Sudden stratospheric warmings (SSW) are large-scale disruptions of the wintertime state of the stratosphere that can affect the circulation at synoptic and global scales, including altitudes up to the mesopause in both winter and summer hemispheres. In this study, the response of the summer mesosphere is analyzed during the SSW in the winter stratosphere. In particular, we focus on major SSW events where the climatological stratopause disappears and subsequently reforms at higher altitude, which we refer to as “extreme SSW” in this article. The summer mesosphere response to such extreme SSW events is analyzed in three different phases: (a) stratosphere warming phase, (b) stratopause discontinuity phase, and (c) stratopause reformation phase. Composites of anomalies with respect to climatology derived from the Microwave Limb Sounder and the extended version of the Whole Atmosphere Community Climate Model with specified dynamics are analyzed. The polar summer mesosphere cools during the stratospheric warming phase and warms in subsequent phases. A detailed lag-correlation analysis shows strong negative correlation of −0.6 to −0.8 between the summer mesosphere and the winter stratosphere during the stratosphere warming phase, and a positive correlation of 0.4–0.6 in the phases thereafter. An attempt is made to explain the apparent drivers and dynamics responsible for these couplings, supported with evidence from observations and model output.